ACCELERATED RECOVERY OF 5-FLUOROURACIL-DAMAGED BONE MARROW AFTER OXYTOCIN TREATMENT - SHADAN MUSLIM ALJANABI; SHAZA AL-LAHAM; ADNAN M. EKHTIAR (International Journal of Pharma and Bio Sciences, 2013)
Our preliminary data indicate that Oxytocin may be myeloprotective. We investigated whether it can modify bone marrow recovery. Oxytocin (150 µg/kg) accelerated the recovery of the number of medium size cells (MI%) and platelets (PLT) but did not affect the number of circulating red blood cells (RBC) and total count of white blood cells (WBC).Oxytocin injected subcutaneously for 5 consecutive days at doses of 150 µg/kg (twice a day) after 5-FU single dose. Glutathione GSH (anti-oxidant) has preventive effects against 5-FU-induced myelosuppression and can accelerate recovery of bone marrow. Oxytocin only increase GSH levels insignificantly (P > 0.05).These findings suggest that Oxytocinselectively enhances the recovery of the population of progenitor cells reduced by 5-FU in rats.